Annotated bird sighting list for summer 1998 compiled by Bery Engebretsen - Engebretsen, Beryet al (1998)
An annotated list of birds sighted by Bery Engebretsen. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1998. Epson - sheet feed/flatbed